Design of compact ultra wideband antenna for microwave medical imaging application - Adib Othman; Nur Ishmah Sabirah Shaari; Abdullah M. Zobilah; Noor Azwan Shairi; Zahriladha Zakaria (Institute of Advanced Engineering and Science, 2019)
A compact ultra wideband (UWB) antenna for operation at 6 GHz intended for microwave medical imaging (MMI) application is proposed. The microstrip patch antenna (MPA) was design in hexagon shape which is contain H-slot at the centre top of the patch and a slot at the ground. Those slots method is utilised to enhance the operating bandwidth as well as minimising the antenna’s impedance mismatch caused by its proximity to material. Results shows that, the implementation of slot on the patch has profoundly enhance the bandwidth (BW) of the antenna to 503.54 MHz. Measurement of fabricated antenna produce significant result in term of producing wide bandwidth of 520 MHz, with slightly shifting on operating frequency. Therefore, it has been proved that the required performance of UWB antenna has been achieved successfully.